Revitalisasi Bahasa Kei Di Era Media Sosial Sebagai Strategi Pendidikan Pascakolonial - Difinubun, Muhar Syahdi (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
The revitalization of the Kei Language faces significant challenges due to the pressures of globalization and the dominance of majority languages; however, the rise of social media provides new opportunities for restoring its social and symbolic functions. This study aims to analyze how the Kei Language is revitalized in the digital era by employing Grenoble & Whaley’s Hybrid/Integrated model, which encompasses three central dimensions: the digital domain, youth agency, and language ideology. Research data were collected through ethnographic observation of TikTok, Instagram, YouTube, and Facebook content that explicitly and implicitly incorporates the Kei Language, complemented by secondary data from language reports and revitalization studies in Maluku. The analysis shows that social media operates as a new linguistic domain that enables the Kei Language to appear in multimodal formats, including text, images, music, memes, customary narratives, and humorous expressions. These findings demonstrate that the revitalization of the Kei Language in the digital era unfolds as an integrative, organic, and participatory process that connects linguistic traditions with modern media ecologies while opening new opportunities for community-based cultural education.